PARADIGMA KH. ALI YAFIE TERHADAP SUMBER- SUMBER HUKUM ISLAM - Sadat, Anwar (DIKTUM: Jurnal Syariah dan Hukum, 2012)
This article reviews the paradigm Yafie KH.Ali thinking about the sources of Islamic law in particular sources of law that has been agreed upon. The method used is a literature review with a direct look at various sources or manuscript is an original work of KH Ali Yafie. Ali Yafie figure was one of the active transform thinking through scholarly writings. Primarily covering the social, political, economic, and health dimensions of Islamic studies (Islamic studies).